Amazwi Amasha: New Approaches to Sustainable Poetry Teaching and Learning - Gerhard Genis; Deirdre C. Byrne (University of Johannesburg, 2024)
At many South African schools poetry is considered  to be a "problem genre", with both teachers and learners viewing it as "difficult" and as a genre that lowers schools' pass rates in the National Senior Certificate (NSC) (Matric) examination. For this reason, schools tend to shy away from prescribing poetry at the Further Education and Training (FET) level (that is, in Grades 10-12). This article argues that the poems that are prescribed for English First Additional Language (EFAL) classes are difficult for learners to relate to because of having been written in contexts that are temporally and geographically distant from the learners' life-worlds. In addition, many learners may not understand the particular variety of English that is used in canonical poetry. A new teaching anthology, entitled Amazwi Amasha (New Voices), containing South African post-1994 poetry, is in the process of being compiled to address the problem of learners' alienation from their prescribed poems. This anthology forms the topic of this article. The theory and methodology underpinning the selection of poems and the design of learning activities to accompany each poem are described, along with the selection of themes that are relevant to young South Africans. The argument concludes that a more multimodal, interactive approach to teaching and learning poetry can help tap into the resources of this capacious and fascinating genre.